IMPLEMENTASI KEBIJAKAN ELECTRONIC TRAFFIC LAW ENFORCEMENT (ETLE) DI KOTA PALU - Abd Haris Ak Mangge; Hartawan Hartawan; Muzakir Tawil (Kampus Akademik Publiser, 2024)
This research aims to find out the implementation of Electronic Policy Traffic Law Enforcemnt (ETLE) in Palu City. The type of research used is qualitative research using descriptive type. The location of this research is Polda Province of Central Sulawesi. The focus of this research is to describe the implementation of the Electronic Traffic Law Enforcement Policy (ETLE) using the policy implementation theory of George Edward III, which covers four elements namely Communication, Resources, Disposition and Bureaucratic Structure. The data collection technique used in this study is through interviews, observations and documentation. The results of this study show that the implementation of the Electronic Traffic Law Enforcment (ETLE) policy in Kota Palu is not effective, because the understanding of the target group (community) about ETLE is still low, the social weakness to the society is finally less understanding the process of ETLE implementation ETLE facilities are not complete as ETLE car cameras are not available and the increase in the number of violations ETLE from 2022 based on the capture of static cameras of 466.491 violations, followed by the capturing of portable violations of 1.601 violations